Analisis Nilai Religi Dalam Cerita Lisan Nyai Sabirah di Desa Bakaran Wetan, Juwana, Pati - Oktaviana Dwi Rahmadhani; Melinda Khoiriyah Ningrum; Sherly Arinda May Listy; Inez Avista Rini; Mohammad Kanzunnudin (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to find the myth, form, and content contained in the folklore of Nyai Sabirah in Bakaran Wetan Village, Juwana Sub-district, Pati Regency, Central Java. The reason for this research is that researchers are interested in myths, customs and traditions in Bakaran Wetan Village. The theory used is Alan's theory where an activity that builds the structure of the Nyai Sabirah story. The research method is descriptive qualitative research, which is located in Bakaran Wetan Village. The data collection technique uses interviews, analysis, direct observation, recording, and recording. Data analysis techniques used with interactive analysis techniques. Then to test the validity of the data using source triangulation. The conclusion of this research is that people in Bakaran Wetan Village still believe in the origin of Nyai Sabirah Folklore. In the folklore of Nyai Sabirah has religious values including faith, love of peace, self-confidence, and firm stance. Although the community believes in the folklore of Nyai Sabirah, the community does not associate God Almighty.